2019
DOI: 10.4236/pst.2019.71001
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Pain Inventory (MPI): Adaptation to Orthodontic Patients and Its Psychometric Properties

Abstract: Background: Pain perception may result from orthodontic treatment and should be considered in clinical management. Its assessment should not be limited to the intensity of perceived pain but should also consider the psychosocial and behavioral aspects involved. Objective: The aims of this study were to adapt and validate the Multidimensional Pain Inventory (MPI) for orthodontic patients, and present a proposal to calculate an overall score of the pain-related aspects and compare these scores with the usual met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 30 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…A limitation of this study includes the lack of clinical evaluation of the participants regarding orthodontic treatment itself, which could have provided additional evidence related to pain. However, it should be clarified that the individual's report often overlaps with the clinical assessment itself because the way an individual perceives pain usually reflects the impact it will have on their life . Therefore, in this study, we decided to focus on the report of pain perception and not the evaluation of nociceptive stimuli, which may be an interesting avenue of investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A limitation of this study includes the lack of clinical evaluation of the participants regarding orthodontic treatment itself, which could have provided additional evidence related to pain. However, it should be clarified that the individual's report often overlaps with the clinical assessment itself because the way an individual perceives pain usually reflects the impact it will have on their life . Therefore, in this study, we decided to focus on the report of pain perception and not the evaluation of nociceptive stimuli, which may be an interesting avenue of investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…To address the first objective of the study, the intensity of pain reported by the patients was assessed using the VAS, and the psychosocial and behavioural aspects of pain perception were assessed using the MPI‐Orthodontic . Both instruments are readily available and have been validated for use in a Brazilian sample population . The VAS consists of a horizontal line, 10 cm in length, with two endpoints labelled "no pain" and "worst ever pain experience."…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations